The role of parental involvement and mathematics self-concept of elementary school students in online mathematics learning - Y. W. Purnomo; N. Apriyanti; S. A. Mubarokah; . Susilowati; W. A. Anggraheni (Образование и наука)
Introduction. Learning mathematics from home during the COVID-19 pandemic is a challenge for both parents and students to manage to engage in learning. Therefore, it is important to examine the involvement of parents in learning mathematics from home and students’ mathematics self-concepts and their relationship to mathematics performance.Aim. This study is aimed to analyse parental involvement and students’ mathematical self-concept, the relationship between the two, and their effect on students’ mathematical performance in online learning.Methodology and research methods. A cross-sectional survey was used to achieve the research objectives. There were 56 elementary school students in rural areas who were involved in this study. To assess parental involvement and mathematics self-concept, the authors employed questionnaires. Meanwhile, the results of the mid-semester test were used to assess student math performance. The answers to the research questions were reported using descriptive analysis, correlation, regression, and the t-test.Results. Based on the results of the analysis, parental involvement, both in terms of support and control aspects, has a significant influence on mathematics performance. On the other hand, mathematics self-concept and performance positively influence each other. The findings of the present research also show that the gender group and grade level group did not have significant differences for each variable.Practical significance. This study has implications for schools to maximise parental involvement in their children’s mathematics learning effectively. Communication between schools, teachers, and children, in particular, becomes critical to maximise children’s potential, including their math self-concept.